Utilization of nano volcanic ash as a natural economical adsorbent for removing cadmium from wastewater - Shoroog Alraddadi (Heliyon, 2022)
The physical properties of volcanic ashes (pumice and scoria) differ based on the locations and historical conditions of the volcanic eruptions, affecting their utilization in applications. In this study, the effectiveness of nano volcanic ash from Al Jabal Al Abyad in eliminating cadmium from aqueous solutions was investigated. Volcanic ash powder was initially milled using a high-energy ball mill to obtain particles with sizes of approximately 500 and 100 nm that were used as adsorbents. The mineralogical and physicochemical properties of the volcanic ash powder were determined using X-ray fluorescence spectroscopy, X-ray diffraction, Raman spectroscopy, and Barrett–Joyner–Halenda analysis. Then, the characteristics of cadmium adsorption (from an aqueous solution) on the volcanic ash powder and nano volcanic ash were determined using atomic absorption spectrophotometry by varying the solution pH, contact time, and initial metal (Cd) ion concentration. Isothermal adsorption and kinetic models were used to determine the analytical potential of the nano volcanic ash. Based on isothermal adsorption analysis, the adsorption capacity increased from 31 to 166 mg/g at pH 6. The adsorption capacity of volcanic ash was much more efficient than that of other natural absorbents owing to its chemical composition, the production of nanoparticles from powdered volcanic ash, and the increase surface area of the adsorbent from 0.293 m2/g to 20.8735 m2/g. The results showed that the adsorption process occurred mainly via monolayer adsorption on the homogeneous adsorbent surface, indicating the validity of the Langmuir adsorption isotherm model. The kinetic model showed that the adsorption of Cd on nano volcanic ash followed the pseudo-second-order kinetic model. The adsorption capacity results indicated that nano volcanic ash from Al Jabal Al Abyad is an applicable candidate and economical adsorbent for removing heavy metals such as cadmium from industrial wastewaters.